Rancang Bangun Mesin Pembuat Deterjen Cair berkapasitas 50 liter/jam - Nidia Lestari (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2018)
Technology continues to grow. Innovations continue to be developed, one of which is innovation on the type of detergent. Liquid detergents are an option used by today's society. The liquid detergent is more soluble than the solid detergent, minimizing the inhalation of solid detergent powder, and does not cause spots on the washing machine. Yogyakarta which is a city of education, attracts young people to come to study. This has an impact on improving the economy of the community. One of them is a laundry business. The design of this machine is done to save business capital where the laundry entrepreneur can make their own liquid detergent, even become the business field of Small and Medium Enterprises. Liquid detergents produced from these machines are better quality, more viscous and the process of mixing raw materials more quickly together and evenly distributed. The use of this machine saves power and time compared to manual or human power where the manufacturing process can be two hours to three hours to stir 50 liters of liquid detergent.